Zero x-rays radiofrequency catheter ablation for ventricular premature contraction originating from the left coronary cusp during pregnancy: a case report - Li, Changjin; Gu, Haoyu; Liu, Chao; Li, Ke; Gao, Xianbu; Yu, Manli; Guo, Zhifu (Frontiers in Cardiovascular Medicine, 2023)
Pregnancy predisposes to arrhythmias in females due to physiological changes in the cardiovascular system, enhanced activity of the sympathetic nervous system (SNS), and changes in the endocrine system, regardless of whether there exist cardiovascular diseases before the pregnancy. Tachyarrhythmias may present for the first time or worsen persistently during pregnancy, potentially leading to maternal heart failure and sudden death, as well as some adverse fetal outcomes such as growth restriction, distress, premature birth, and stillbirth. Radiofrequency ablation (RFA) is one of the most important therapeutic methods for tachyarrhythmias. According to the 2019 European Society of Cardiology (ESC) guidelines, RFA in pregnant women should preferably be performed without x-rays. Since the 2000s, 3D mapping technique has rapidly developed, laying the foundation for cardiac electrophysiology examination free from x-rays. Ventricular arrhythmia originating from the left coronary cusp (LCC) is not common in clinic. RFA is challenging in the treatment of this type of disease due to the anatomical feature that the opening of the left main coronary artery is localized in the LCC.